Lessons learned from pre-service teachers when implementing the lesson study approach and inquiry-based learning - Irene Muller (AOSIS, 2024)
Background: In the training of pre-service teachers a collaborative lesson study approach was implemented as a teaching strategy, with citizen science as a teaching tool and incorporation of sustainable developmental goals (SDGs). Aim: The aim of the research was to determine to what extent the lesson study approach (LSA) enabled pre-service teachers to plan lessons in natural science. Setting: The research was executed at a higher educational institute situated on a campus in an industrial area next to a large river in Gauteng province, South Africa. Methods: In this participatory action learning and action research pre-service teachers, as co-researchers, indicated their experience when collaborate planning, reflect and present lessons. Results: The pre-service teachers indicated that the LSA allowed to acknowledge diversity in knowledge and learning. They reported to gain skills like problem-solving, systemic thinking and communication. Inclusion of citizen science and SDGs enhance education for sustainable development. Conclusion: The inclusion of the LSA has cognitive and affective gains which outcast the challenges of timing and resources. Contribution: The LSA allows for pre-service teachers to work collaboratively in lesson planning and allows for the inclusion of unique teaching tools such as citizen science and SDGs.